ORAL HEALTH TRAINING USING â€œPOSLEAâ€ MEDIA TO EMPOWER PARENTS AND TEACHERS IN SUPPORTING DENTAL CARE FOR VISUAL IMPAIRMENT CHILDREN - Aprilinda Pipit Ruswita; Muh Taufiq Seftiadi; Endah Aryati Eko Ningtyas (Poltekkes Kemenkes Semarang, 2025)
Visual impairment children have challenges in maintaining oral hygiene due to limited visual abilities. Parents and teachers play a critical role in guiding these children to improve their dental health. This study aims to evaluate the effectiveness of oral health training using the â€œPOSLEAâ€ media in enhancing parents and teachers knowledge and improving the toothbrushing skills of visual impairment children. The study was conducted at SLB Negeri Jepara from September to October 2024. Subjects included 18 visual impairment students, 8 teachers, and parents. Data were collected through questionnaires, observations, and debris index assessments before and after the training. The training program consisted of material delivery, simulations, and hands-on practice using audio and braille-based media. The results revealed a significant increase in knowledge among parents (72% in the â€œgoodâ€ category) and teachers (100% in the â€œgoodâ€ category) after the training. Additionally, the toothbrushing skills of students improved from the â€œneeds assistanceâ€ category to 89% of students achieving the â€œexcellentâ€ category. The training effectively facilitated understanding of proper toothbrushing techniques for all tooth surfaces and their application in daily routines. In conclusion, oral health training using the â€œPOSLEAâ€ media is effective in empowering parents and teachers to support the dental health of visually impaired children. Continuous monitoring is recommended to ensure the sustained positive impact of this training.